The Influence of Work Environment and Work Motivation on Work Stress at PT Sigma Cipta Company - Muhammad Revansyah Prama Swabhowo; Rony Edward Utama (MES Bogor, 2025)
The purpose of this research is to investigate and evaluate how employee job stress at PT Sigma Cipta Utama is impacted by the work environment and work motivation. Employee job stress is the dependent variable in this research, whilst work environment and motivation are the independent factors.Thirty-three respondents who work at PT Sigma Cipta Utama were given questionnaires in order to gather data. major data served as the major data source for this research, which used a quantitative approach using an associative technique. With the use of the SPSS software, multiple linear regression analysis was used to analyze the data.With a significance level of less than 0.05 and a t value bigger in absolute terms than the t table value (|−6.822| > 2.042), the study's findings show that the work environment has a negative and substantial impact on employee job stress. Additionally, job Motivation has a negative and substantial impact on employee job stress, with a significance level of less than 0.05 and a t value that is higher in absolute terms than the t table value (|−3.975| > 2.042). The F value is more than the F table value (52.088 > 3.32) and the significance level is less than 0.05, indicating that the job Environment and Work Motivation have a substantial impact on employee job stress simultaneously.